2018
DOI: 10.1515/hmbci-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization (WHO) versus The International Association of Diabetes and Pregnancy Study Group (IADPSG) diagnostic criteria of gestational diabetes mellitus (GDM) and their associated maternal and neonatal outcomes

Abstract: Background Gestational diabetes mellitus (GDM) is a common medical complication in pregnancy. The aim of this study was to compare the prevalence of GDM using the World Health Organization (WHO) criteria and the International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria in our population. We further compared the incidence of adverse maternal and neonatal outcomes in women diagnosed with GDM using these criteria and determined whether the IADPSG criteria is suitable in our population. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 15 publications
0
40
4
1
Order By: Relevance
“…Although we did not use the IADPSG criteria for our cohort, the low prevalence of fasting abnormalities among our women was unlikely to affect the overall study findings. A previously published study from our institution found no significant difference in the prevalence of GDM between the women diagnosed using the 1999 WHO (fasting ≥6.1 mmol/L, 2-h ≥7.8 mmol/L) and IADPSG (fasting ≥5.1 mmol/L, 2-h ≥8.5 mmol/L) criteria [ 18 ], a result that could be attributed to the higher rate of postprandial abnormality in our population.…”
Section: Discussioncontrasting
confidence: 49%
“…Although we did not use the IADPSG criteria for our cohort, the low prevalence of fasting abnormalities among our women was unlikely to affect the overall study findings. A previously published study from our institution found no significant difference in the prevalence of GDM between the women diagnosed using the 1999 WHO (fasting ≥6.1 mmol/L, 2-h ≥7.8 mmol/L) and IADPSG (fasting ≥5.1 mmol/L, 2-h ≥8.5 mmol/L) criteria [ 18 ], a result that could be attributed to the higher rate of postprandial abnormality in our population.…”
Section: Discussioncontrasting
confidence: 49%
“…Nonetheless, most studies reported an increase in the number of GDM cases [15][16][17][18][19][20] , although some studies reported similar or decreased in number of GDM cases. 21,22 This reduction reflected that most GDM cases detected in the Chinese population was by the 2HG test. Therefore, a decrease in the number of GDM cases detected was due to the loosening of the 2HG test.…”
Section: Discussionmentioning
confidence: 94%
“…As our results showed, the current literature also demonstrated that women with gestational diabetes are at risk of both maternal, fetal and neonatal adverse outcomes, including pre-eclampsia and eclampsia (8-fold raise), increased risk of preterm birth, higher need for labor induction, caesarean section, stillbirths, macrosomia, full term low weight infants, newborns large for gestational age, neonatal morbidity (namely hyperbilirubinemia and jaundice, respiratory distress and asphyxia, hypoglycemia and congenital malformations), increased need to admission in neonatal intensive care unit and neonatal death (5-fold raise). 2,11,16 However, there are also some studies that do not share the same scientific opinion. Some authors stated that the prevalence of newborns large for gestational age, cesarean section and preterm deliveries in gestational diabetes was not elevated.…”
Section: Discussionmentioning
confidence: 99%
“…35 This same finding is concordant with the results of the present study, which showed that maternal obesity doesn't seem to be an aggravating factor of gestational diabetes, which could be explained by the greater number of prenatal visits and strict vigilance of women with gestational diabetes that should be enough to achieve a more rigorous diet and weight control, as already mentioned in the recent literature. 2,4,11 In the same way, other authors considered advanced maternal age as a potential risk factor of gestational diabetes, as well as an aggravating factor of it, capable to raise the incidence of adverse outcomes for mothers, newborns and infants, as spontaneous late preterm deliveries, fetal growth restriction, small for gestational age infants and birthweight < 2500 g. 3,14,21 However, according to some authors, maternal age does not significantly influence birthweight. 25 Despite the findings in the literature, the present study did not find advanced maternal age as an aggravating factor of gestational diabetes, which could be explained also by a more rigorous vigilance of these pregnant women.…”
Section: Discussionmentioning
confidence: 99%